2015
DOI: 10.1080/01626620.2014.971136
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Courage: Fostering the Development of Critical, Social Justice-Oriented Teachers Using Museum and Project-Based Instruction

Abstract: Through course readings, museum visits, focus group discussions, and reflections on clinical observation experiences, preservice teachers developed a fictitious educational setting (Courage High School) that incorporates critical, social justice practices and privileges the experiences and cultural backgrounds of all K-12 students. Participants presented a model for this school and how it would benefit specific student needs. From our classroom experiences, the authors developed recommendations for how future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For example, Coffey et al (2015) reported that TCs focused on “an appreciation for diversity of linguistic, ethnicity, gender, sexual orientation, socio-economic status, intellectual and physical disability, and learning styles” (p. 15) as they created a fictitious “courageous” high school; unclear is whether the terms learning modalities, learning styles , or multiple intelligences also signaled disability, and if so, in what ways. Of the 96 NCATE conceptual frameworks that included social justice investigated by Kapustka et al (2009), only one was reported to address disability, by preparing TCs to be “sensitive to students with special needs” (p. 500).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Coffey et al (2015) reported that TCs focused on “an appreciation for diversity of linguistic, ethnicity, gender, sexual orientation, socio-economic status, intellectual and physical disability, and learning styles” (p. 15) as they created a fictitious “courageous” high school; unclear is whether the terms learning modalities, learning styles , or multiple intelligences also signaled disability, and if so, in what ways. Of the 96 NCATE conceptual frameworks that included social justice investigated by Kapustka et al (2009), only one was reported to address disability, by preparing TCs to be “sensitive to students with special needs” (p. 500).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Coffey, Fitchett, and Farinde (2015) suggest candidates should explore the relationship between “race, class, and schooling” (p. 11); their work also fosters an “appreciation for diversity of linguistic, ethnicity, gender, sexual orientation, socioeconomic status, intellectual and physical ability, and learning styles” (p. 15). Taylor and Sobel (2003) state that today teachers must “address factors of culture, language, ethnicity, race, ability, gender, socioeconomic level, religion, age, and sexual orientation” (p. 249), alongside their repeated focus on multicultural, multilingual, and inclusive education.…”
Section: Resultsmentioning
confidence: 99%
“…More common was the practice of acknowledging intersectionality but not elaborating upon it, which occurred in eight studies, or 15%. For example, in studying courageous teaching, Coffey et al (2015), citing a secondary source, conclude that one implication of their inquiry is that faculty “might actually generate conversations about the intersectionality of oppression produced and proliferated in American schooling (and in teacher education)” (p. 19). Skerrett (2010) specifically describes her TCs’ growing understandings of the influences of multiple social markers, stating that “this includes who in society gets to determine class, how class boundaries are enforced, and the ways that class is influenced by other social markers such as gender and race” (p. 58).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not only nursing students that need to develop critical thinking, cultural safety and an anti-racist orientation. Academia must also foster the development of critical, antiracist oriented educators who are able to step out of the rigidity of curricular standardization and take a leap of faith in which the teaching for anti-oppression becomes a principal instructional goal (Coffey et al, 2015). Such a leap of faith requires training for academics, including clinical instructors, professors and administrators as well.…”
Section: Implications For Educationmentioning
confidence: 99%